Deraeocoris schach, a new predator of Euphydryas aurinia and other heteropteran feeding habits on caterpillar web (Heteroptera: Miridae; Lepidoptera: Nymphalidae) - Pinzari, Manuela (Fragmenta entomologica, 2016)
In this paper, preliminary results on a field study aiming to identify predators of the Marsh Fritillary Euphydryas aurinia (Rottemburg, 1775) in Central Italy are presented. Several heteropterans were found on the larval nests of E. aurinia for dietary reasons: Deraeocoris schach (Fabricius, 1781) that is a predator of Marsh Fritillary larvae, Palomena prasina (Linnaeus, 1761) and Spilostethus saxatilis (Scopoli, 1763) that feed on the droppings of larvae; Graphosoma lineatum italicum (Müller, 1766) that visits the larval web during winter diapause.